(untitled) (Journal of Informatics Education and Research, 2025)
Digital trade has been one of the domains which have been severely lacking between India and the US, both governments have therefore started devising plans that can help in using technology as a major platform for cooperation. The purpose of the present research has been to closely observe the digital trade scenario between both countries and the policy barriers and concerns which limit digital trade between both countries. Secondary sources of information from peer-reviewed journals, online articles from top media houses and government reports have been used to address the purpose of the study and collect the necessary data. The different policy barriers identified by CCIA have been studied within the research to show the imbalance and misalignment of digital trade, and adequate opportunities have been discussed to increase cross border digital trade between India and the US.